1-18v+11=-19v+19

Simple and best practice solution for 1-18v+11=-19v+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-18v+11=-19v+19 equation:


Simplifying
1 + -18v + 11 = -19v + 19

Reorder the terms:
1 + 11 + -18v = -19v + 19

Combine like terms: 1 + 11 = 12
12 + -18v = -19v + 19

Reorder the terms:
12 + -18v = 19 + -19v

Solving
12 + -18v = 19 + -19v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '19v' to each side of the equation.
12 + -18v + 19v = 19 + -19v + 19v

Combine like terms: -18v + 19v = 1v
12 + 1v = 19 + -19v + 19v

Combine like terms: -19v + 19v = 0
12 + 1v = 19 + 0
12 + 1v = 19

Add '-12' to each side of the equation.
12 + -12 + 1v = 19 + -12

Combine like terms: 12 + -12 = 0
0 + 1v = 19 + -12
1v = 19 + -12

Combine like terms: 19 + -12 = 7
1v = 7

Divide each side by '1'.
v = 7

Simplifying
v = 7

See similar equations:

| g(x)=ln[(7x+4)*5] | | -18-6k=-6(k+3) | | 5y=10-12x | | 6(u+3)=3u+12 | | 8x-9-15= | | 1+19f=6f+7+12f | | 1.5x+1y=10 | | -4(5t-4)+5t=2t-4 | | (6x+y^2)dx+y(2x+3y)dy=o | | f(n)=n^4 | | 2x+(-7-x)=-1 | | 1x+6(36-5x)=2 | | 10x+45=5x+12 | | 0=-16(X^2)+(120X)+100 | | 10+6x=1x | | p-p-18=-p+2 | | 5x+6=-8+2x+20 | | 0=-16(X^2)+(120X)+25 | | -8-8x+10+6x=18 | | 6.1a+15=63.8 | | -19+13r+17=14r-11 | | X-4=-x-4 | | 0=-16X^2+120X+25 | | 7g+2=33 | | X-68=23 | | 16z-19=8z+17+5z | | (2x+1)+(3x+10)+68=180 | | 2+8.3x=4.6+4.2x | | 7j+2=3 | | -6-9+17q=19q+11 | | 5.77x+1=33.2929+x | | S=54-.08(54) |

Equations solver categories